A Holocene tephra layer within coastal aeolian deposits north of Caleta Olivia (Santa Cruz Province, Argentina) - Zanchetta, Giovanni (2021)
In this paper we illustrate the stratigraphy, geochronology, and geochemistry (major, minor, trace elements and Sr-isotopes) of a Holocene tephra layer found within coastal sedimentary deposits north of Caleta Olivia (Santa Cruz Province, Argentina). The stratigraphic succession comprises beach deposits with basal erosive surface resting on the local substrate (“Formacion Patagonia”) followed by a poorly developed paleosoil. The paleosoil is covered by a lenticular fine-grained (Mdφ: 5.2, 0.027 mm), well sorted (σφ: 1.2) volcanic ash layer and aeolian sands. The geochemical composition of shard fragments points to an origin from the Hudson volcano, located in the southern Andes, ca. 400 km to the west. The geochemistry, Sr-isotopes and the radiometric constraints (younger than the age of the underlying marine layer dated at ca. 4,100 a cal BP) further allow correlating this tephra with the so-called H2 eruption (ca. 3,900 a cal BP). This finding is of interest owing to the poor preservation potential of tephra within the Late Holocene sedimentary deposits of the Atlantic coast of Patagonia and represents the first finding of H2 eruption in this area, improving our knowledge of the dispersion of the fine-grained distal deposit of the Hudson volcanic explosive activity, thus allowing a better estimate of the eruptive dynamics and the risks associated with the Hudson volcano.